PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN GRAB(Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Negeri Makassar) - Alvina Asyhafa; Nurman, Muhammad Ilham Wardhana, Hasbiah, Muhammad Ichwan Musa (CV. ADIBA AISHA AMIRA, 2023)
The purpose of this study aims to determine the effect of service quality on Grab consumer satisfaction among students of the Faculty of Economics and Business, Makassar State University. The population in this study is all consumers who use the Grab application, namely 100 for 3 months. The sample in this study is all users of the Grab application for students of the Faculty of Economics and Business, Makassar State University Class of 2018. Overall this research shows that the respondents' assessment of this research variable, namely Service Quality (X), is generally good. This is indicated by the many agreeing responses from respondents to the research variable, namely the independent variable Grab service quality on consumer satisfaction in students of the Faculty of Economics and Business, Makassar State University. Based on the results of this study, it can be concluded that service quality has a positive effect on Grab consumer satisfaction in 100 respondents at the Faculty of Economics and Business, Makassar State University